Reasons why women present with late stages of cervical cancer at Chris Hani Baragwanath academic hospital - Mbodi, Langanani (My University, 2016)
Background and objectives Current estimates of the number of new cases of cervical cancer in South Africa suggest that there are about 5743 new cases and 3027 deaths from the disease per year. It is still unclear or poorly defined why women present late. The purpose of this study was to determine the stages of cervical cancer that women present with at Chris Hani Baragwanath Academic Hospital and to identify factors associated with late presentation. Methods This was a prospective study conducted at all the gynecology units of the O& G department at CHBAH in Soweto, Gauteng Province over 12 months period between January and December 2013. Results A total of 111 women were recruited into the study. Only 104 women were included in the study. Two (2) women withdrew due to personal reasons. Three (3) women were excluded as their fully histology report could not be retrieved. Two (2) women could not continue with the interview due to pain and discomfort. x The mean age of women was 50.2 years (SD±12.30) with an IQR of 40.50-49.50. The mean ages for stage 1 were 42.22 (SD±10.34), 51.00 (SD±12.54) for stage 2, 51.60 (SD±12.34) for stage 3 and 47.10 (SD±13.35) for stage 4 [p-value of 0.16]. The majority of women (67.31%) in our study are from a poor socio-economic environment with a combined family earning of less than three thousands rand. Abnormal vaginal bleeding was the commonest reason for consultation (48.54%). 43 women (41.75%) first discussed the problems with their family members for input and advice before consulting any healthcare facility. Almost 48% of women still do not know about Pap smear. Conclusion Women with late stages of cervical cancer are more likely to be older than 50 years, come from a low socio-economic background and more likely to have not completed high school. There is an increase in incidences of adeno-carcinoma presenting with stages 3 and 4 of the disease. Vaginal bleeding remain the commonest symptom and probably a red flag for cervical cancer in post-menopausal women. However, many women delay seeking healthcare in our public health facility even after identifying the signs and symptoms suggestive of cervical cancer. We speculate discussing with family members and seeking opinion could be the result for delayed consultation. There is a need to continued education on cervical cancer warning signs and screening programs.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Masters of Medicine in the branch of Obstetrics and Gynaecology FCOG (SA) Johannesburg, 2016
Keywords: Women; Uterine Cervical Neoplasms